Preparation method of reduced graphene oxide coated iron-based Prussian blue sodium ion battery positive electrode material
By coating the surface of iron-based Prussian blue sodium-ion battery cathode material with reduced graphene oxide, the problems of structural instability and low conductivity of the material were solved, resulting in higher cycle stability and electrochemical performance, and improving the overall performance of sodium-ion batteries.
Patent Information
- Application Number
- CN202511267713.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2025-12-02
AI Technical Summary
Existing iron-based Prussian blue sodium-ion battery cathode materials suffer from problems such as short cycle life, low conductivity, and high interfacial impedance, making it difficult for their actual performance in sodium batteries to meet industrialization requirements.
The iron-based Prussian blue material is coated with reduced graphene oxide (rGO) to form a continuous coating layer, which blocks the direct contact between the electrolyte and Fe-PBA, reduces the reaction between lattice water and electrolyte, enhances mechanical strength, resists volume deformation, and extends battery life.
It significantly improves the cycle stability and electrochemical performance of the material, extends battery life, and enhances the charge/discharge efficiency and rate performance of sodium-ion batteries.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing iron-based Prussian blue sodium-ion battery cathode material coated with reduced graphene oxide, belonging to the technical field of sodium-ion battery cathode materials. Background Technology
[0002] Sodium-ion batteries are cheaper than lithium-ion batteries, especially in terms of positive and negative electrode materials. Sodium-ion batteries typically use low-cost materials such as sodium manganese oxide or hard carbon, which are more economical than lithium cobalt oxide and nickel cobalt manganese oxide used in lithium-ion batteries. In addition, compared with lithium-ion batteries, sodium-ion batteries have advantages such as high safety performance, excellent low-temperature performance, and good rate performance. Sodium-ion batteries also have a smaller environmental impact during production and recycling.
[0003] Cathode materials are crucial components of sodium-ion batteries. Currently, the three main technological routes for sodium-ion battery cathode materials include polyanionic compounds, transition metal layered oxides, and Prussian blue analogues. Among these, Prussian blue-based materials, with their open framework structure, high theoretical specific capacity, and energy-efficient synthesis process, are highly suitable as cathode materials for sodium-ion batteries. Current research focuses on iron-based and manganese-based Prussian blue materials. Iron-based Prussian blue analogues (Fe-PBA), with their unique advantages, have become a key research direction for sodium battery cathode materials: their three-dimensional open pore structure (pore size approximately 0.3-0.5 nm) can precisely match the Na+... + The migration requirement (ionic radius 0.102nm) can provide a theoretical specific capacity of 120-170mAh / g, and the raw materials (such as ferric chloride and sodium ferrocyanide) are inexpensive. The preparation process can be completed by aqueous solution precipitation, without the need for high-temperature sintering, which meets the cost and process requirements of industrialization.
[0004] Although Fe-PBA is compatible with sodium-ion cathodes, its inherent structure and the special nature of sodium-ion working environment make it difficult for its actual performance to meet industrialization needs. The core defects are concentrated in the following three aspects: (1) Crystal defects and structural instability lead to short cycle life; (2) Low conductivity and high interface impedance restrict rate performance and efficiency; (3) The limitations of modification schemes in sodium-ion scenarios. Summary of the Invention
[0005] To address the aforementioned technical problems with Prussian blue sodium-ion battery cathode materials, this invention provides a method for preparing iron-based Prussian blue sodium-ion battery cathode materials coated with reduced graphene oxide (rGO). The rGO two-dimensional sheet structure forms a continuous coating layer on the surface of Fe-PBA particles, preventing direct contact between the electrolyte and Fe-PBA, avoiding the reaction of lattice water with the electrolyte to generate hydrofluoric acid (a corrosive substance), and reducing the loss of active sites and electrolyte contamination. rGO possesses excellent mechanical strength (Young's modulus of approximately 1 TPa), which can withstand the reaction of Fe-PBA in Na+. + The volume deformation during the insertion / deinsertion process reduces the cycle volume expansion rate from 20-35% to 3-6%, avoiding particle disintegration and significantly extending battery life.
[0006] A method for preparing a reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material, the specific steps of which are as follows: (1) Under a protective atmosphere, sodium ferrocyanide, complexing agent, and sodium salt are completely dissolved in deionized water to obtain solution A; (2) Under a protective atmosphere, iron salt, complexing agent and sodium salt are completely dissolved in deionized water to obtain solution B; (3) Under a protective atmosphere, solution B was added dropwise to solution A, and a co-precipitation reaction was carried out at a temperature of 20~60℃ with stirring. The mixture was then allowed to stand at room temperature for 8~48h, and the solid and liquid were separated. The solid was washed with deionized water and anhydrous ethanol in sequence, and then dried under vacuum to obtain the precursor Fe-PBA. (4) The precursor Fe-PBA and reduced graphene oxide were ball-milled and coated, and then heat-treated under a protective atmosphere to obtain reduced graphene oxide coated iron-based Prussian blue sodium-ion battery cathode material.
[0007] Preferably, in step (1), the concentration of sodium ferrocyanide in solution A is 0.06~0.1mol / L, the molar ratio of the amount of complexing agent added to sodium ferrocyanide is 2~3:10, and the molar ratio of sodium salt to sodium ferrocyanide is 2~15:12.
[0008] Preferably, the complexing agent in steps (1) and (2) is sodium citrate, disodium ethylenediaminetetraacetate, sodium pyrophosphate, or sodium acetate, and the sodium salt is sodium sulfate or sodium chloride.
[0009] Preferably, the iron salt in step (2) is one or more of ferric chloride, ferric sulfate, ferric nitrate, and ferric acetate.
[0010] Preferably, the molar ratio of the iron salt in step (2) to the sodium ferrocyanide in step (1) is 18~32:24.
[0011] Preferably, in step (2), the concentration of iron salt in solution B is 0.06~0.1mol / L, the molar ratio of the amount of complexing agent added to iron salt is 2~3:10, and the molar ratio of sodium salt to iron salt is 2~15:12.
[0012] Preferably, in step (3), the dropping rate of solution B is 30~50 ml / h; the vacuum drying temperature is 60~85℃, and the time is 12~36 h.
[0013] Preferably, in step (4), the mass ratio of the precursor Fe-PBA to the reduced graphene oxide is 1:0.03~0.08; the mass ratio of the ball material to the ball mill is 10:1~3, the rotation speed is 400~600 rpm, and the time is 1~3h.
[0014] Preferably, the protective atmosphere in step (4) is nitrogen or an inert gas, the heat treatment temperature is 135~180℃, and the time is 15~48h.
[0015] The beneficial effects of this invention are: (1) In this invention, a complexing agent is used to assist in the co-precipitation synthesis of heterogeneous lattice-stabilized Prussian blue analogues. When the complexing agent is added to ferrocyanide ions for reaction, it effectively reduces the precipitation rate and the crystallization reaction occurs slowly. By adjusting the amount of complexing agent and the titration rate, the crystallinity of the particles can be controlled to obtain a product with stable structure and few defects. (2) The present invention obtains sodium-ion battery cathode material by coating reduced graphene oxide (rGO) with Prussian blue analogues, which effectively suppresses the volume change of iron-based Prussian blue analogue particles during cycling, prevents structural collapse, effectively improves the cycle stability of cathode material during charging and discharging, and improves the electrochemical performance of sodium-ion battery. Attached Figure Description
[0016] Figure 1 SEM image of the iron-based Prussian blue sodium electrode material in Example 1; Figure 2 SEM images of comparative iron-based Prussian blue sodium electrode materials; Figure 3 Charge-discharge curves of iron-based Prussian blue sodium cathode materials in comparative examples and Examples 1-3; Figure 4 The discharge long-cycle performance diagrams are for the comparative examples and Examples 1-3 of the iron-based Prussian blue sodium cathode materials; Figure 5 This is a rate performance diagram of the iron-based Prussian blue sodium electrode material in Example 1. Detailed Implementation
[0017] The present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the content described.
[0018] Example 1: A method for preparing a reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material, the specific steps of which are as follows: (1) Under a nitrogen atmosphere, sodium ferrocyanide Na4Fe(CN)6·10H2O, complexing agent (sodium citrate), and sodium salt (Na2SO4) are completely dissolved in deionized water to obtain solution A; the molar ratio of the complexing agent (sodium citrate) to sodium ferrocyanide is 3:10, the molar ratio of sodium salt (Na2SO4) to sodium ferrocyanide is 1:6, and the concentration of sodium ferrocyanide in solution A is 0.06 mol / L; (2) Under a nitrogen atmosphere, iron salt (FeSO4·7H2O), complexing agent (sodium citrate), and sodium salt (Na2SO4) are completely dissolved in deionized water to obtain solution B; the molar ratio of iron salt (FeSO4·7H2O) to sodium ferrocyanide in step (1) is 1:1, the molar ratio of the amount of complexing agent (sodium citrate) added to iron salt (FeSO4·7H2O) is 3:10, the molar ratio of sodium salt (Na2SO4) to iron salt (FeSO4·7H2O) is 1:6, and the concentration of iron salt (FeSO4·7H2O) in solution B is 0.06 mol / L; (3) Solution B was added dropwise to solution A at a rate of 30 mL / h. The co-precipitation reaction was carried out under nitrogen atmosphere, temperature of 25℃ and stirring for 8 h. The solid was then aged at room temperature for 24 h. The solid was separated from the liquid and washed three times each with deionized water and anhydrous ethanol. The solid was then dried under vacuum at 60℃ for 12 h to obtain the precursor Fe-PBA. (4) The precursor Fe-PBA and reduced graphene oxide rGO (the mass ratio of precursor Fe-PBA to reduced graphene oxide rGO is 1:0.05) were ball-milled for 2 hours (the mass ratio of ball to material in ball milling is 10:3, and the rotation speed is 400 rpm). Then, the mixture was heat-treated at a protective atmosphere (nitrogen atmosphere) and a temperature of 150°C for 24 hours to obtain the reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material, denoted as Fe-PBA@5%rGO. The SEM image of the reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material Fe-PBA@5%rGO in this embodiment is shown below. Figure 1 ,from Figure 1 It can be seen that the main particles exhibit a regular morphology of approximately polyhedra. The rGO coating layer was roughened but maintained its original shape, reflecting that the Fe-PBA matrix has good crystallinity. The regular crystal structure is the cornerstone of material properties. The rough surface and dispersed small particles can increase the contact area between the electrode and the electrolyte, which is beneficial to Na + Rapid adsorption / desorption enhances rate performance.
[0019] Comparative Example 1: The difference between the comparative example and Example 1 is that in step (4), the precursor Fe-PBA is directly heat-treated to prepare an iron-based Prussian blue analog sodium cathode material, denoted as Fe-PBA; SEM images of comparative iron-based Prussian blue analog sodium cathode material Fe-PBA are shown below. Figure 2 ,from Figure 2 It can be seen that the prepared PB nanocubes have a typical cubic shape and a rough surface.
[0020] Example 2: A method for preparing a reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material, the specific steps of which are as follows: (1) Under an argon atmosphere, sodium ferrocyanide Na4Fe(CN)6·10H2O, complexing agent (disodium ethylenediaminetetraacetate), and sodium salt (NaCl) are completely dissolved in deionized water to obtain solution A; the molar ratio of the complexing agent (disodium ethylenediaminetetraacetate) to sodium ferrocyanide is 1:4, the molar ratio of sodium salt (NaCl) to sodium ferrocyanide is 5:4, and the concentration of sodium ferrocyanide in solution A is 0.08 mol / L; (2) Under an argon atmosphere, iron salt (FeCl2·4H2O), complexing agent (disodium ethylenediaminetetraacetate), and sodium salt (NaCl) are completely dissolved in deionized water to obtain solution B; the molar ratio of iron salt (FeCl2·4H2O) to sodium ferrocyanide in step (1) is 6:8, the molar ratio of the amount of complexing agent (disodium ethylenediaminetetraacetate) to iron salt (FeCl2·4H2O) is 1:4, the molar ratio of sodium salt (NaCl) to iron salt (FeCl2·4H2O) is 5:4, and the concentration of iron salt (FeCl2·4H2O) in solution B is 0.08 mol / L; (3) Solution B was added dropwise to solution A at a rate of 40 mL / h. The co-precipitation reaction was carried out for 12 h under an argon atmosphere, a temperature of 30 °C and stirring. The mixture was then allowed to stand and age at room temperature for 30 h. The solid and liquid were separated. The solid was washed three times each with deionized water and anhydrous ethanol. It was then vacuum dried at 70 °C for 24 h to obtain the precursor Fe-PBA. (4) The precursor Fe-PBA and reduced graphene oxide rGO (the mass ratio of precursor Fe-PBA to reduced graphene oxide rGO is 1:0.03) were ball-milled for 1 h (the mass ratio of ball to material in ball milling is 10:1, and the rotation speed is 500 rpm). Then, the mixture was heat-treated at a protective atmosphere (argon atmosphere) and a temperature of 160 °C for 48 h to obtain the reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material, denoted as Fe-PBA@3%rGO.
[0021] Example 3: A method for preparing a reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material, the specific steps of which are as follows: (1) Under a nitrogen atmosphere, sodium ferrocyanide Na4Fe(CN)6·10H2O, complexing agent (sodium pyrophosphate), and sodium salt (NaCl) are completely dissolved in deionized water to obtain solution A; the molar ratio of the complexing agent (sodium pyrophosphate) to sodium ferrocyanide is 1:5, the molar ratio of sodium salt (NaCl) to sodium ferrocyanide is 1:1, and the concentration of sodium ferrocyanide in solution A is 0.1 mol / L; (2) Under a nitrogen atmosphere, iron salt (Fe(NO3)3·9H2O), complexing agent (sodium pyrophosphate), and sodium salt (NaCl) are completely dissolved in deionized water to obtain solution B; the molar ratio of iron salt (Fe(NO3)3·9H2O) to sodium ferrocyanide in step (1) is 8:6, the molar ratio of the amount of complexing agent (sodium pyrophosphate) added to iron salt (Fe(NO3)3·9H2O) is 1:5, the molar ratio of sodium salt (NaCl) to iron salt (Fe(NO3)3·9H2O) is 1:1, and the concentration of iron salt (Fe(NO3)3·9H2O) in solution B is 0.1 mol / L; (3) Solution B was added dropwise to solution A at a rate of 50 mL / h. The co-precipitation reaction was carried out for 10 h under nitrogen atmosphere, temperature of 40 °C and stirring. The solid was then aged at room temperature for 48 h. The solid was separated from the liquid and washed three times each with deionized water and anhydrous ethanol. The solid was then vacuum dried at 85 °C for 36 h to obtain the precursor Fe-PBA. (4) The precursor Fe-PBA and reduced graphene oxide rGO (the mass ratio of precursor Fe-PBA to reduced graphene oxide rGO is 1:0.08) were ball-milled for 3h (the mass ratio of ball to material in ball milling is 10:1.5, and the rotation speed is 600rpm), and then heat-treated at a protective atmosphere (nitrogen atmosphere) and a temperature of 180℃ for 24h to obtain the reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material, denoted as Fe-PBA@8%rGO; Battery Assembly: Using the reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery positive electrode material of Comparative Example 1 and Examples 1-3 as the active material, the active material, SuperP carbon black (conductive additive), and polyvinylidene fluoride (PVDF) binder were mixed uniformly to obtain a mixture. The mass ratio of active material, SuperP carbon black (conductive additive), and PVDF in the mixture was 7:2:1. N-methyl-2-pyrrolidone (NMP) solvent was gradually added and stirred to obtain a uniformly dispersed positive electrode slurry. The positive electrode slurry was uniformly coated onto a clean aluminum foil current collector, and the N-methyl-2-pyrrolidone solvent was removed by vacuum drying to obtain an electrode film. The electrode film was subjected to cold pressing to improve the adhesion between particles, and then stamped into a disc electrode. The average mass loading of the active material (iron-based Prussian blue sodium-ion battery positive electrode material) on the disc electrode was 1.2~1.5 mg / cm³. 2 The disk electrode was quickly transferred to an argon-filled glove box (H2O / O2<0.1ppm), and a CR2032 button cell was assembled using sodium metal as the counter electrode and glass fiber as the positive electrode. The constant current charge and discharge test voltage window of the CR2032 button cell was 2-4.2V. The charge-discharge curves of the iron-based Prussian blue sodium-ion battery cathode materials in the comparative examples and Examples 1-3 at a current density of 1C are shown below. Figure 3 ,from Figure 3 It can be seen that different samples (Comparative Example 1, Example 1, Example 2, Example 3) exhibit different potentials (relative to Na / Na) during the charging and discharging process. + The relationship between specific capacity and the curves is shown. Overall, the several examples exhibited superior electrochemical performance during charge and discharge, possibly because their material structure or composition is more conducive to sodium ion insertion / extraction, resulting in more stable voltage changes during charge and discharge and achieving higher potentials. This has a positive impact on key performance characteristics of sodium-ion batteries, such as energy density. Comparative Example 1, on the other hand, showed relatively poor performance, possibly due to inherent material factors that hinder sodium ion transport or storage. The discharge long-cycle performance graphs of the Prussian blue sodium cathode materials in the comparative examples and Examples 1-3 at a current density of 1C are shown below. Figure 4 ,from Figure 4 It can be seen that the initial discharge specific capacity of the uncoated comparative sample was 121.53 mAh g−1, but only 63.8% of the capacity was retained after 200 cycles. The main reason is the structural degradation caused by lattice water and Fe. 2+Dissolution; the electrodes of Examples 1-3, coated with rGO, exhibited significantly enhanced stability, attributed to the high sodium content filling the lattice vacancies of Fe-PBA, combined with the mechanical buffering effect of the rGO coating layer, reducing the material's cyclic volume expansion rate and preventing particle disintegration. In Example 1, the iron-based Prussian blue sodium cathode material with a 5% rGO coating achieved an initial discharge specific capacity of 116.37 mAh g⁻¹ and maintained 85.8% capacity retention after 200 cycles, indicating that Example 1 has good cycling performance. The initial capacities of the iron-based Prussian blue sodium cathode materials with a 3% rGO coating in Example 2 and the iron-based Prussian blue sodium cathode materials with an 8% rGO coating in Example 3 were 120.36 mAh g⁻¹, respectively. −1 and 118.17mAhg −1 The initial discharge specific capacity of Examples 2 and 3 was higher than that of Example 1, but the capacity retention rates of Examples 2 and 3 were lower than those of Example 1, at 62.32% and 71.7% respectively, indicating that their cycle stability was poor. Example 1: Rate performance diagram of iron-based Prussian blue sodium cathode material (see Figure 1) Figure 5 When the rate is increased to 2C, 5C or even 10C, although the discharge specific capacity decreases (to a lower value at 10C), after returning to a low rate of 0.1C, the discharge specific capacity recovers significantly (close to the initial low rate level). This indicates that the ion transport network inside the material (such as the through-channel constructed by rGO) is challenged at high rates, but it does not completely collapse. After returning to a low rate, it can operate efficiently again, indicating that the enhancement effect of rGO coating on electron transport has reversible controllability.
[0022] The specific embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.
Claims
1. A method for preparing a reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material, characterized in that, The specific steps are as follows: (1) Under a protective atmosphere, sodium ferrocyanide, complexing agent, and sodium salt are completely dissolved in deionized water to obtain solution A; (2) Under a protective atmosphere, iron salt, complexing agent and sodium salt are completely dissolved in deionized water to obtain solution B; (3) Under a protective atmosphere, solution B was added dropwise to solution A, and a co-precipitation reaction was carried out at a temperature of 20~60℃ with stirring. The mixture was then allowed to stand at room temperature for 8~48h, and the solid and liquid were separated. The solid was washed with deionized water and anhydrous ethanol in sequence, and then dried under vacuum to obtain the precursor Fe-PBA. (4) The precursor Fe-PBA and reduced graphene oxide were ball-milled and coated, and then heat-treated under a protective atmosphere to obtain reduced graphene oxide coated iron-based Prussian blue sodium-ion battery cathode material.
2. The method for preparing the reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material according to claim 1, characterized in that: In step (1), the concentration of sodium ferrocyanide in solution A is 0.06~0.1mol / L, the molar ratio of the amount of complexing agent added to sodium ferrocyanide is 2~3:10, and the molar ratio of sodium salt to sodium ferrocyanide is 2~15:
12.
3. The method for preparing the reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material according to claim 1, characterized in that: In steps (1) and (2), the complexing agent is sodium citrate, disodium ethylenediaminetetraacetate, sodium pyrophosphate or sodium acetate, and the sodium salt is sodium sulfate or sodium chloride.
4. The method for preparing the reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material according to claim 1, characterized in that: Step (2) The iron salt is one or more of ferric chloride, ferric sulfate, ferric nitrate, and ferric acetate.
5. The method for preparing the reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material according to claim 1, characterized in that: The molar ratio of iron salt in step (2) to sodium ferrocyanide in step (1) is 18~32:
24.
6. The method for preparing the reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material according to claim 1, characterized in that: In step (2), the concentration of iron salt in solution B is 0.06~0.1mol / L, the molar ratio of the amount of complexing agent added to iron salt is 2~3:10, and the molar ratio of sodium salt to iron salt is 2~15:
12.
7. The method for preparing the reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material according to claim 1, characterized in that: In step (3), the dropping rate of solution B is 30~50 ml / h; the vacuum drying temperature is 60~85℃, and the time is 12~36 h.
8. The method for preparing the reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material according to claim 1, characterized in that: Step (4) The mass ratio of precursor Fe-PBA to reduced graphene oxide is 1:0.03~0.08; the mass ratio of ball material to ball milling material is 10:1~3, the rotation speed is 400~600rpm, and the time is 1~3h.
9. The method for preparing the reduced graphene oxide-coated iron-based Prussian blue sodium-ion battery cathode material according to claim 1, characterized in that: Step (4) The protective atmosphere is nitrogen or inert gas, and the heat treatment temperature is 135~180℃ for 15~48h.
Citation Information
Patent Citations
Prussian blue / reduced graphene oxide composite material as well as preparation method and application thereof
CN104716314A
Preparation and application of carbon-coated sodium-iron-based Prussian blue positive electrode material
CN114709402A
Organic solvent post-treated Prussian blue sodium ion battery positive electrode material and preparation method and application thereof
CN115458740A
Carbon-coated bluish blue material, positive pole piece, preparation method of positive pole piece and sodium ion battery
CN117334856A